Heart immunoengineering by lentiviral vector-mediated genetic modification during normothermic ex vivo perfusion - Schmalkuche, Katharina; Rother, Tamina; Burgmann, Jonathan M.; Voß, Henrike; Höffler, Klaus; Dogan, Günes; Ruhparwar, Arjang; Schmitto, Jan D.; Blasczyk, Rainer; Figueiredo, Constanca (Frontiers in Immunology, 2024)
Heart transplantation is associated with major hurdles, including the limited number of available organs for transplantation, the risk of rejection due to genetic discrepancies, and the burden of immunosuppression. In this study, we demonstrated the feasibility of permanent genetic engineering of the heart during ex vivo perfusion. Lentiviral vectors encoding for short hairpin RNAs targeting beta2-microglobulin (shβ2m) and class II transactivator (shCIITA) were delivered to the graft during two hours of normothermic EVHP. Highly efficient genetic engineering was indicated by stable reporter gene expression in endothelial cells and cardiomyocytes. Remarkably, swine leucocyte antigen (SLA) class I and SLA class II expression levels were decreased by 66% and 76%, respectively, in the vascular endothelium. Evaluation of lactate, troponin T, and LDH levels in the perfusate and histological analysis showed no additional cell injury or tissue damage caused by lentiviral vectors. Moreover, cytokine secretion profiles (IL-6, IL-8, and TNF-α) of non-transduced and lentiviral vectortransduced hearts were comparable. This study demonstrated the ex vivo generation of genetically engineered hearts without compromising tissue integrity. Downregulation of MHC expression may contribute to reduce the immunogenicity of the heart and support graft survival after allogeneic or xenogeneic transplantation.Recently, the heart has become a major target for gene therapy to prevent heart failure. Beneficial effects of VEGF-A, VEGF-B, or SDF-1 gene therapy have been described in pre-clinical trials. These approaches were based on the application of adenoviral vectors or adeno-associated viral (AAV) vectors by arterial and venous infusion, direct myocardial injection, and pericardial injection as administration routes, resulting in localized genetic modification of the cardiac tissue (7-9). So far, lentiviral vectors have been less exploited due to their poor stability and complex manufacturing process, yielding low titers. However, lentiviral vectors mediate the permanent expression of delivered transgenes (10-12).